Assessing the quality of green open spaces: a review - Abdul Malek, Nurhayati; Mariapan, Manohar; Mohd Shariff, Mustafa Kamal; Aziz, Azlizam (2010)
The fundamentals of urban open space management suggest that a thoughtfully implemented urban development should include more than just great buildings. It should include parks and open spaces because both buildings and open spaces benefit from each other through the quality of each space. Furthermore, it provides benefits from the economical, social, communal, environmental and aesthetical aspects. Parks and open spaces improved the quality of life of cities and neighbourhood by the city amenities and facilities. The conceptual framework on quality of a neighbourhood park in this paper is derived from a multidisciplinary study in the fields of landscape architecture, leisure, recreation, tourism and environment. This framework allows for theory-based consolidation of facts and ideas as well as practical implications for the development of tools to evaluate the aspects of quality in a Malaysian neighbourhood park. Neighbourhood park was chosen as the subject of assessment for this tool because it has social, economic and cultural values on our everyday lives. Not only does it provide revenue benefits for health and mental well-being, it also serves as a societal and community’s meeting place for certain residential neighbourhood. This paper critically reviews the outcome of analyses literature that defines the concept of quality for a neighbourhood park. The result from this study is being used to guide future research regarding the development of a framework to define aspects of quality in Malaysian local parks.